Genome-Wide Identification and Characterization of the Mitochondrial Transcription Termination Factors (mTERFs) in Capsicum annuum L. - Tang, Bingqian (Int J Mol Sci, 2019)
Mitochondrial transcription termination factors (mTERFs) regulate the expression of mitochondrial genes and are closely related to the function of the mitochondrion and chloroplast. In this study, the mTERF gene family in capsicum (Capsicum annuum L.) was identified and characterized through genomic and bioinformatic analyses. Capsicum was found to possess at least 35 mTERF genes (CamTERFs), which were divided into eight major groups following phylogenetic analysis. Analysis of CamTERF promoters revealed the presence of many cis-elements related to the regulation of cellular respiration and photosynthesis. In addition, CamTERF promoters contained cis-elements related to phytohormone regulation and stress responses. Differentially expressed genes in different tissues and developmental phases were identified using RNA-seq data, which revealed that CamTERFs exhibit various expression and co-expression patterns. Gene ontology (GO) annotations associated CamTERFs primarily with mitochondrion and chloroplast function and composition. These results contribute towards understanding the role of mTERFs in capsicum growth, development, and stress responses. Moreover, our data assist in the identification of CamTERFs with important functions, which opens avenues for future studies.